Reconciling the estimates of potential migration into the enlarged European Union - Anzelika Zaiceva (Institute for the Study of Labor (IZA), 2006)
This paper briefly reviews the existing literature on potential migration into the enlarged European Union, reconciles the results with recent evidence and presents an additional migration scenario. The estimation procedure accounts for both sending and receiving countries' unobserved heterogeneity, and in the simulations a counterfactual scenario is calculated, in which all EU member states introduce free movement of workers simultaneously in 2011. The results suggest that the overall level of migration from the East will amount to around 1 per cent of the EU15 population within a decade after enlargement, and that the legal introduction of free movement of workers will not increase immigration significantly. These findings are compared both with the previous literature and emerging evidence.
urn:nbn:de:101:1-20080502116
Keywords: 330